Modulation of the thalamus by microburst vagus nerve stimulation: a feasibility study protocol - Verner, Ryan; Szaflarski, Jerzy P.; Allendorfer, Jane B.; Vonck, Kristl; Giannicola, Gaia; , Microburst Study Group; McDermott, Danielle; Brown, Mesha Gay; Kaye, Lesley; Macken, Michael; Tatum, William O.; Drees, Cornelia; et al. (Frontiers in Neurology, 2023)
Vagus nerve stimulation (VNS) was the first device-based therapy for epilepsy, having launched 1994 in Europe and 1997 in the United States. Since that time, significant advances in understanding of the mechanism of action of VNS and the central neurocircuitry that VNS modulates have impacted how the therapy is practically implemented. However, there has been little change to VNS stimulation parameters since the late 1990s. Short bursts of high frequency stimulation have been of increasing interest to other neuromodulation targets e.g., spine, and these high frequency bursts elicit unique effects in the central nervous system when applied to the vagus nerve. We describe a protocol design that aims to assess the impact of high frequency bursts of stimulation, called “Microburst VNS”, in subjects with refractory focal and generalized epilepsies treated with this novel stimulation pattern in addition to standard anti-seizure medications. This protocol also employs an investigational, fMRI-guided titration protocol that permits personalized dosing of Microburst VNS among the treated population depending on the thalamic blood-oxygen-level-dependent signal. The study was registered on clinicaltrials.gov (NCT03446664). The first subject was enrolled in 2018 and the final results are expected in 2023.